1995
DOI: 10.1161/01.cir.91.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Previous Angina Alters In-Hospital Outcome in TIMI 4

Abstract: Previous angina confers a beneficial effect on in-hospital outcome after acute myocardial infarction. The reasons for this benefit are uncertain, but one potential mechanism for this observation may be ischemic preconditioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
166
1
5

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 487 publications
(184 citation statements)
references
References 26 publications
8
166
1
5
Order By: Relevance
“…Most recently, the fourth Thrombolysis in Myocardial Infarction (TIMI-4) study group have observed that patients with a history of unstable angina 24 to 48 h before acute myocardial infarction had lower mortality following infarction than those patients who had no previous history of angina. The halving of mortality rate in these patients could not be accounted for by changes in collateral blood supply or anti-anginal medication [69].…”
Section: Preconditioning Models In Human Myocardium In Situmentioning
confidence: 85%
“…Most recently, the fourth Thrombolysis in Myocardial Infarction (TIMI-4) study group have observed that patients with a history of unstable angina 24 to 48 h before acute myocardial infarction had lower mortality following infarction than those patients who had no previous history of angina. The halving of mortality rate in these patients could not be accounted for by changes in collateral blood supply or anti-anginal medication [69].…”
Section: Preconditioning Models In Human Myocardium In Situmentioning
confidence: 85%
“…The presence of PIA reported in the literature varies widely, with some studies even showing an inverse proportion [5][6][7][8][9] .…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have found a decrease in ventricular remodeling 5 , as well as in the incidence of ventricular arrhythmias, congestive heart failure (CHF), cardiogenic shock, and death [6][7][8] . Reperfusion of the infarctrelated artery was also found to be faster after thrombolytic therapy when AMI was preceded by PIA 9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 For example, clinical observation has shown that the occurrence of episodes of angina shortly before a myocardial infarction reduces mortality and morbidity. 4,5 In the setting of percutaneous transluminal coronary angiography, it has been shown that measures of ischemia, such as angina and ST elevation, in the ECG occurring during the period when the coronary artery is occluded by the inflated balloon are less during a second balloon inflation compared with the first. 6 -8 These studies are not always easy to interpret, however, because of confounding variables such as uncertainties about the recruitment of collaterals in response to the preconditioning ischemia, the adequacy of the very short…”
mentioning
confidence: 99%